2019
DOI: 10.1177/0003319719870950
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrocardiographic Left Ventricular Hypertrophy and Resting Heart Rate Over Time: Findings From the OGHMA Study

Abstract: Both elevated resting heart rate (HR) and electrocardiographic left ventricular hypertrophy (ECG-LVH) are signs of a poor prognosis. Although elevated resting HR is a known risk factor for cardiovascular disease and target organ damage, the association between resting HR and the development of ECG-LVH is unclear. In the present study, 6860 subjects (4203 men, 2657 women, 19-89 years of age) without ECG-LVH at baseline were evaluated and followed for a mean duration of 3.7±1.4 years. During the follow-up period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
0
6
2
Order By: Relevance
“…Moreover, Inoue et al . reported an inverse association between resting heart rate and the development of electrocardiographic LV hypertrophy 33 . However, we are unable to explain why these findings differ from the reported association of increased heart rate with increased CVD incidence, including HF incidence, and all‐cause mortality 7,34–36 .…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Moreover, Inoue et al . reported an inverse association between resting heart rate and the development of electrocardiographic LV hypertrophy 33 . However, we are unable to explain why these findings differ from the reported association of increased heart rate with increased CVD incidence, including HF incidence, and all‐cause mortality 7,34–36 .…”
Section: Discussioncontrasting
confidence: 67%
“…reported an inverse association between resting heart rate and the development of electrocardiographic LV hypertrophy 33 . However, we are unable to explain why these findings differ from the reported association of increased heart rate with increased CVD incidence, including HF incidence, and all‐cause mortality 7,34–36 . The mechanisms by which increased heart rate was associated with a lower risk of isolated structural abnormality, and a lower risk of diastolic abnormality, despite the positive association between BP and diastolic abnormality, remain to be defined.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, related studies in Egypt and Greece reported that LVH was reversely related to HR 38,39 . Additionally, the finding from the OGHMA study in Japan reported that each 10 beats/min increase in resting HR was associated with reduced development of ECG-LVH, especially among males 40 . Nevertheless, the temporal relationship between resting HR and developing ECG-LVH in the present study could not be proved due to the cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%
“…We have noticed a correlation between a lower HR and LVH. Inoune [47] showed a similar dependence, in which an elevated resting HR was negatively associated with the development of ECG LVH in a healthy male group. We explain this correlation by more common use of beta-blockers among individuals with LVH, who more frequently had a history of HA, myocardial infarction (MI), CHD, and AF.…”
Section: Clinical and Biochemical Factorsmentioning
confidence: 70%